Proceedings of the Sixth Padang International Conference on Economics Education, Economics, Business and Management, Accounting 2021
DOI: 10.2991/aebmr.k.210616.050
|View full text |Cite
|
Sign up to set email alerts
|

Readiness to Implement Digital Learning

Abstract: WHO announced the Covid-19 as Global Pandemic in early 2020? This condition immediately urged universities to migrate their instructional process to fully online learning as a result of the suggestion of physical distancing. This situation indeed results in the shock of the culture of learning and teaching. Following its shock, of course, questions arise related to the readiness of higher education in implementing fully online learning. This study aims to measure the readiness of lecturers and students of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 26 publications
0
6
0
1
Order By: Relevance
“…In regard to this, Traxler (2007) suggests that higher education tends to have better readiness for IT integration in academic programs due to better availability of infrastructures and accessibility to knowledge. Further, Sagala, Hasibuan, et al (2021) similarly fi nd that the readiness of higher education teaching staff for online learning is quite adequate, despite a few technical problems during the early process of shifting to a new learning mode.…”
Section: Introductionmentioning
confidence: 96%
See 4 more Smart Citations
“…In regard to this, Traxler (2007) suggests that higher education tends to have better readiness for IT integration in academic programs due to better availability of infrastructures and accessibility to knowledge. Further, Sagala, Hasibuan, et al (2021) similarly fi nd that the readiness of higher education teaching staff for online learning is quite adequate, despite a few technical problems during the early process of shifting to a new learning mode.…”
Section: Introductionmentioning
confidence: 96%
“…Various studies have reported the eff ectiveness of using IT in improving the quality of learning. Interestingly, due to the Covid-19 pandemic, IT mediation has become immensely dominant, as it completely replaces the full time face-to-face classroom meetings (Hardini, Setyarini, & Harto, 2021;Sagala, Hasibuan, & Suharianto, 2021;Siswanto, Kartanegara, & Chuan, 2021). Nevertheless, online learning remains a diff erent concept from the IT-integrated approach aimed to optimize learning.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations